2008
DOI: 10.4102/ojvr.v75i1.90
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Peganum harmala</i> (wild rue) extract on experimental ovine malignant theileriosis : pathological and parasitological findings

Abstract: Malignant theileriosis of sheep is a highly fatal, acute or subacute disease is caused by the tick-borne protozoan parasite, Theileria hirci. In this investigation ten healthy male lambs aged 5-6 months were randomly divided into two groups, A and B and were kept in isolated tick-proof pens. They were treated for internal and external parasite before commencement of the experiment. The lambs were experimentally infected with T. hirci by placing ticks Hyalomma anatolicum anatolicum infected with T. hirci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Total alkaloids of P. harmala seeds have been shown to have therapeutic effect on the bovine babesiosis and theileriosis (Fan et al 1997), bovine natural tropical theileriosis (Mirzaei 2007) and ovine malignant theileriosis (Derakhshanfar and Mirzaei 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Total alkaloids of P. harmala seeds have been shown to have therapeutic effect on the bovine babesiosis and theileriosis (Fan et al 1997), bovine natural tropical theileriosis (Mirzaei 2007) and ovine malignant theileriosis (Derakhshanfar and Mirzaei 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[52] Further, ability to generate cysteine and ultimately glutathione, can additionally contribute to its potential free radical scavenger activity. [53] Type 2 diabetes mellitus (T2DM) is characterized by altered insulin signaling and we observed a decrease in insulin level in HFD + low dose STZ-induced T2DM rats, indicating animals are in chronic diabetic condition. At the initial stage of obesity-induced T2DM, hyperinsulinemia is caused by the compensatory increase of -cell mass by -cell neogenesis, -cell replication (hypertrophy), and decrease in -cell apoptosis to enhance the -cell performance in order to maintain glucose level.…”
Section: Discussionmentioning
confidence: 73%
“…Derakhshanfar et al [58] infected 5-6-month-old lambs with T. hirci, and treated them with the extracts of the aerial parts of P. harmala at a dose of 5 mg/kg. Microscopic observation showed that the parasites disappeared in 9 days and the rectal temperature returned to normal in the lymph nodes and peripheral blood smears of lambs in the treatment group.…”
Section: Antiparasitic Activitymentioning
confidence: 99%